THE ACQUISITION OF FOREIGN LANGUAGE BY STUDENTS WITH INTELLECTUAL DISABILITY IN AN ELEMENTARY SCHOOL - Poļaka, Anna (Education Reform: Education Content Research and Implementation Problems, 2019)
The aim of the research: to investigate development opportunities of the acquisition English by the students with intellectual disability of class 6 and 9 and to analyze results of research and work out conclusions. It was analyzed information from literature sources about the organization of the learning process for students with intellectual disability and the feature of teaching English to students with intellectual disability in the theoretical part of the research. The empirical part of this paper was conducted during a year (from May 2018 to May 2019). The participants in this study are nine males and females with mild retardation.